2014
DOI: 10.1097/coc.0b013e31827e4e7b
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma Outcomes and Prognostic Factors

Abstract: Objective Angiosarcoma is an aggressive malignancy with endothelial differentiation and notoriously poor prognosis despite aggressive therapy. Limited data are available to guide management decisions. To address this limitation, we present a large retrospective analysis of angiosarcoma patients treated at a single institution over a 25-year period. Methods To identify factors that impact angiosarcoma outcomes, we reviewed demographic, tumor and treatment characteristics of angiosarcoma patients evaluated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
97
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 36 publications
10
97
5
Order By: Relevance
“…Strikingly in our series, C-AS affecting the scalp and face comprised 95% of C-AS, and two-thirds of the entire cohort. This contrasts with reports in other series of Western patients with AS where scalp or cutaneous head and neck AS, though forming the majority of head and neck AS, comprises only between 20 and 37% of all patients with AS [10,21]. It has been suggested that AS of the scalp is more common in Asian as compared with Western patients; our data certainly supports this observation.…”
Section: Discussioncontrasting
confidence: 57%
“…Strikingly in our series, C-AS affecting the scalp and face comprised 95% of C-AS, and two-thirds of the entire cohort. This contrasts with reports in other series of Western patients with AS where scalp or cutaneous head and neck AS, though forming the majority of head and neck AS, comprises only between 20 and 37% of all patients with AS [10,21]. It has been suggested that AS of the scalp is more common in Asian as compared with Western patients; our data certainly supports this observation.…”
Section: Discussioncontrasting
confidence: 57%
“…Angiosarcoma is a rare and aggressive soft tissue sarcoma arising in vascular endothelial cells, and is a disease with poor prognosis and reported five-year overall survival rates in the range 30% - 40% [181]. Although no standard treatment exists, the majority of patients are treated with surgical resection, chemotherapy (doxorubicin or paclitaxel most commonly) and radiotherapy [182].…”
Section: Our Takementioning
confidence: 99%
“…Canine hemangiosarcoma and human angiosarcoma are both vasoformative sarcomas with similar microscopic appearance [13] that have often metastasized by the time they are diagnosed. Humans with angiosarcoma have an expected median survival of approximately 16 months [14]; dogs with HSA have a comparable, short median survival of 4 to 6 months when treated with the standard-of-care of surgery and adjuvant chemotherapy [15, 16]. Morbidity and mortality are usually caused by metastatic spread and/or acute internal hemorrhage secondary to tumor rupture.…”
Section: Introductionmentioning
confidence: 99%